The right to education and the work of convicts: An interruption between needs and possibilities - Tanjević Nataša (Trendovi u Poslovanju)
Education, professional training and work during the execution of a prison sentence may be an important factor in achieving positive changes in the behavior of convicts and reducing the risk of recidivism. In this regard, in this work we pointed out the need for these activities and importance for the rehabilitation of convicts and the reduction of recidivism, as well as the problems and challenges in the realization of educational and working activities that occur in practice. It was concluded that the implementation of normative solutions is hampered by the fact that spatial, personnel and material conditions in prisons are unsatisfactory, and that in conditions where the educational and working parts of the treatment are not being implemented or the content of these activities are at a low level it is difficult to expect an effective execution of the prison sentence.